Low-modulus high-strength metastable beta titanium alloy and preparation method and application thereof
Ti-Zr-Mo low-mode high-strength metastable β-titanium alloy prepared by laser additive manufacturing technology solves the problem of insufficient stress shielding effect and strength of metal implants in the human body, and achieves high intensity in biomedical applications Matching with low modulus reduces the risk of loosening and toxicity of the implant.
Patent Information
- Application Number
- CN202411445964.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-03
AI Technical Summary
The problems of "stress shielding effect" and insufficient strength caused by mismatch of elastic modulus in the human body, especially in bone implants, lead to implant looseness and toxicity risks.
Through laser additive manufacturing technology, low-mode high-strength metastable β-titanium alloy with Ti-Zr-Mo component is prepared, and multiple coaxial powder feeding and laser directional energy deposition are adopted, combined with solid solution quenching treatment to optimize the gradient mechanical properties of the alloy. , obtain a titanium alloy with low-mode and high-strength performance.
It has achieved the reduction of the occurrence of "stress shielding effect" in biomedical applications and provided sufficient strength support, with an elastic modulus of 59.9~74.2GPa, a yield strength of 800~880MPa, a tensile strength of 840~950MPa, and an elongation of 840~950MPa. 13%~20%, meeting the needs of implants.
Smart Images

Figure CN119242987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser additive manufacturing, and in particular to a low-modulus high-strength metastable β titanium alloy and a preparation method and application thereof. Background Art
[0002] Based on the advantages of personalized and precise customization of additive manufacturing, the medical application of metal implants has developed rapidly. The "Regulations on the Supervision and Administration of Customized Medical Devices" jointly issued by the National Medical Products Administration and the National Health Commission clearly listed additively manufactured medical devices as formal means of clinical diagnosis and treatment. Ti6Al4V alloy has the advantages of good corrosion resistance and high specific strength, making it a widely used metal material for additive manufacturing load-bearing bone implants. However, its elastic modulus (about 110 GPa) is significantly higher than the human bone modulus (up to only 30 GPa). After implantation into the human body, it will bear the main stress to form a "stress shielding" effect, causing the adjacent bone to be absorbed and causing the implant to loosen and fail. In addition, the Al and V elements contained in Ti6Al4V have the risk of dissolution in the human environment, causing toxicity to the nervous system, etc.: Al element accumulation can lead to diseases such as Alzheimer's disease, and V element accumulation can induce immunotoxicity. Therefore, it is urgent to develop low-modulus and high-strength bio-titanium alloys to ensure the long-term safe service of load-bearing bone implants.
[0003] In recent years, metastable β bio-titanium alloy has become the preferred material for the new generation of metal implants because of its bio-toxicity and modulus that can be well matched with human bones. Studies have pointed out that the strength of implants is the key to determining their fatigue life. Under long-term complex stress in the body, implants are prone to fracture due to insufficient strength. The development of low-modulus, high-strength metastable β bio-titanium alloys has become a new breakthrough in the current research on load-bearing bone implant materials. The literature "Mitsuo Niinomi, Fatigue performance and cyto-toxicity of low rigidity titanium alloy, Ti-29Nb-13Ta-4.6Zr, Biomaterials, 2003, 24 (16): 2673-2683." reported that the elastic modulus of Ti-29Nb-13Ta-4.6Zr alloy is 65GPa, but the yield strength is only 600MPa, and the tensile strength is only 650MPa, which is much lower than the strength of Ti6Al4V alloy. The patent with announcement number CN 200410092858.1, “A superelastic low modulus titanium alloy and preparation and processing method”, stabilizes the β phase and reduces the elastic modulus by adding metals such as Nb. The alloy is improved in strength through complex forging and rolling processes, but it is not suitable for the customized features of bone implants and the near-net forming of complex structures. At present, most alloys add relatively expensive metals such as Nb and Ta, and the trial and error method is mostly used in the alloy design stage, and multiple components are prepared for experimental testing. However, laser additive manufacturing technology can be used to prepare gradient alloys, and at the same time, the β matrix can be regulated in situ, which can achieve the coordinated regulation of the modulus and strength of the metastable β bio-titanium alloy, and select low-modulus and high-strength titanium alloys suitable for additive manufacturing. At the same time, it can achieve personalized customization of bone implants and near-net forming of complex structures, providing important support for the functional improvement and structural integration of metal implants. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technologies, the present invention mainly solves the problems of "stress shielding effect" and insufficient strength generated by implants during service. The present invention provides a low-modulus, high-strength metastable β-titanium alloy and a preparation method and application thereof. The present invention explores a low-modulus, high-strength titanium alloy composition specifically for laser additive manufacturing by combining high-throughput experimental technology and directed energy deposition technology. A Ti-Zr-Mo composition gradient alloy is prepared in situ by multi-channel coaxial powder feeding, and the change in the gradient mechanical properties of the alloy is characterized by hardness. The low value point of the hardness curve is selected as the composition point to obtain a metastable β-titanium alloy with low modulus and high-strength performance.
[0005] The first object of the present invention is to provide a low modulus high strength metastable β titanium alloy, which is composed of the following components by mass fraction: Mo 10.5%-12%, Zr 20%-25%, and the balance Ti.
[0006] Preferably, the elastic modulus of the low modulus, high strength, metastable β titanium alloy is 59.9-74.2 GPa.
[0007] Preferably, the yield strength of the low modulus high strength metastable β titanium alloy is 800-880 MPa, the tensile strength is 840-950 MPa, and the elongation is 13%-20%.
[0008] Preferably, the alloy structure of the low modulus, high strength metastable β titanium alloy in the deposited state and the solid solution quenched state is β phase.
[0009] The second object of the present invention is to provide a method for preparing a low modulus high strength metastable β titanium alloy, comprising the following steps: Mixing Ti powder, Zr powder and Mo powder according to a certain proportion to obtain a mixed powder; or preparing a TiZrMo component pre-alloyed powder; After the mixed powder or pre-alloyed powder is vacuum dried, a sample is formed on a pure titanium substrate by laser directed energy deposition or laser powder bed melting. After forming, a solution quenching treatment is performed to obtain a low-modulus and high-strength metastable β titanium alloy.
[0010] Preferably, when Ti powder, Zr powder and Mo powder are mixed according to a certain proportion, the process comprises: Ti powder, Zr powder and Mo powder were weighed according to the proportion and loaded into an agate ball mill jar, and then put into a planetary ball mill for mixing. The parameters were set to a frequency of 25 Hz and a time of 120 minutes.
[0011] Preferably, when the powder is deposited by laser directed energy deposition, the process parameters include: The laser spot diameter is 5 mm, the laser power is 3400~3800 W, the laser beam scanning speed is 8~10 mm / s, the overlap rate is 50%, the powder feeding rate is 10~15 g / min, the gas flow rate is 4~5 L / min, and the nozzle lifting height per layer is 0.6~0.8 mm; Wherein, when using the laser directed energy deposition method, the particle size of the Ti powder, Zr powder, and Mo powder in the mixed powder or the particle size of the pre-alloyed powder is 75-150 μm.
[0012] Preferably, during the solution quenching treatment, the solution temperature is 750-850° C. and the solution time is 40-120 min.
[0013] Preferably, the process parameters for preparing high-strength titanium alloy workpieces by laser powder bed fusion are: The laser spot diameter is 60 μm, the laser power is 200~240W, the laser scanning speed is 1000~1500 mm / s, the layer thickness is 30~45 μm, and the scanning line distance is 80~100 μm; Among them, when using the laser powder bed melting method, the particle size of the Ti powder, Zr powder, Mo powder or pre-alloyed powder in the mixed powder is 15~53μm.
[0014] The third object of the present invention is to provide a low modulus high strength metastable β titanium alloy for use in biomedicine, aerospace, automobile manufacturing or machinery manufacturing.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a low-modulus high-strength metastable β titanium alloy and its preparation method and application. The titanium alloy provided by the present invention does not add expensive alloying elements such as Nb and Ta, and does not require complex forging, hot rolling and other process measures. It can directly complete near-net forming through additive manufacturing and post-heat treatment, so that the microstructure of the final formed titanium alloy is mainly β phase. Finally, after laser directional energy deposition forming and solid solution quenching, an elastic modulus of 59.9~74.2GPa, a yield strength of 800~880MPa, a tensile strength of 840~950MPa and a high elongation of 13%~20% can be directly obtained. Its mechanical properties can meet the needs of implants in biomedicine, can effectively reduce the occurrence of "stress shielding effect" and provide sufficient strength support. The results of the present invention have broad application prospects in the field of biomedicine and can significantly improve production efficiency and economic benefits.
[0016] The present invention provides a design method for the composition and process of a low modulus, high strength metastable β titanium alloy. By combining high-throughput experimental technology and directed energy deposition technology, a low modulus, high strength titanium alloy composition dedicated to laser additive manufacturing is explored. A Ti-Zr-Mo composition gradient alloy is prepared in situ by multi-channel coaxial powder feeding, and the change of the alloy gradient mechanical properties is characterized by hardness. The low value point of the hardness curve is selected as the composition point to obtain a metastable β titanium alloy with low modulus and high strength performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a Ti-Zr-Mo gradient titanium alloy formed by laser directed energy deposition; Figure 2 It is a Ti-Zr-Mo gradient titanium alloy formed by laser directed energy deposition, (a) composition change curve; (b) hardness change curve; Figure 3 It is the microstructure of a part of the Ti-Zr-Mo gradient titanium alloy formed by laser directed energy deposition; Figure 4 is the microstructure of the composition Ti-24Zr-11Mo prepared in Example 1; Figure 5 is the diffraction spot of the Ti-24Zr-11Mo alloy prepared in Example 1; Figure 6 is the tensile mechanical property curve of the Ti-24Zr-11Mo alloy prepared in Example 1; Figure 7 is the tensile stress-strain curve of the Ti-24Zr-11Mo alloy prepared in Example 2; Figure 8 This is the XRD spectrum of the Ti-24Zr-11Mo alloy prepared in Example 3. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0019] The purpose of the present invention is to provide a low-modulus, high-strength metastable β bio-titanium alloy and a laser additive manufacturing screening method thereof, so as to solve the problems of "stress shielding effect" and insufficient strength generated by implants during service.
[0020] In order to achieve the above object, the first aspect of the present invention provides a low modulus, high strength, metastable β titanium alloy, which is composed of the following components by mass fraction: Mo 10.5%-12%, Zr 20%-25%, and the balance Ti.
[0021] Wherein, the elastic modulus of the low modulus and high strength metastable β titanium alloy is 59.9~74.2GPa.
[0022] The low modulus high strength metastable β titanium alloy has a yield strength of 800-880 MPa, a tensile strength of 840-950 MPa, and an elongation of 13%-20%.
[0023] The alloy structure of the low-modulus high-strength metastable β titanium alloy in the deposited state and the solid solution quenched state is β phase.
[0024] The low-modulus, high-strength metastable β titanium alloy is prepared by an additive manufacturing method and subsequent heat treatment.
[0025] A second aspect of the present invention provides a method for preparing a low modulus high strength metastable β titanium alloy, comprising the following steps: Mixing Ti powder, Zr powder and Mo powder according to a certain proportion to obtain a mixed powder; or preparing a TiZrMo component pre-alloyed powder; After the mixed powder or pre-alloyed powder is vacuum dried, a sample is formed on a pure titanium substrate by laser directed energy deposition or laser powder bed melting. After forming, a solution quenching treatment is performed to obtain a low-modulus and high-strength metastable β titanium alloy.
[0026] Wherein, when Ti powder, Zr powder and Mo powder are mixed according to a proportion, it includes: Ti powder, Zr powder and Mo powder were weighed according to the proportion and loaded into an agate ball mill jar, and then put into a planetary ball mill for mixing. The parameters were set to a frequency of 25 Hz and a time of 120 minutes.
[0027] Specifically, when the powder is deposited by laser directed energy deposition, the process parameters include: The laser spot diameter is 5 mm, the laser power is 3400~3800 W, the laser beam scanning speed is 8~10 mm / s, the overlap rate is 50%, the powder feeding rate is 10~15 g / min, the gas flow rate is 4~5 L / min, and the nozzle lifting height per layer is 0.6~0.8 mm; Wherein, when using the laser directed energy deposition method, the particle size of the Ti powder, Zr powder, and Mo powder in the mixed powder or the particle size of the pre-alloyed powder is 75-150 μm.
[0028] Among them, during the solution quenching treatment, the solution temperature is 750~850℃, and the solution time is 40~120min.
[0029] The process parameters for preparing high-strength titanium alloy workpieces by laser powder bed fusion are: The laser spot diameter is 60 μm, the laser power is 200~240W, the laser scanning speed is 1000~1500 mm / s, the layer thickness is 30~45 μm, and the scanning line distance is 80~100 μm; Among them, when using the laser powder bed melting method, the particle size of the Ti powder, Zr powder, Mo powder or pre-alloyed powder in the mixed powder is 15~53μm.
[0030] It should be noted that the pre-alloyed powder is prepared by first smelting Ti, Zr and Mo metals into an alloy and then powdering and forming the pre-alloyed powder. The process for preparing the pre-alloyed powder can be gas atomization, plasma rotating electrode method, radio frequency plasma spheroidization method, etc.
[0031] In one embodiment, a method for preparing a low modulus high strength metastable β titanium alloy comprises the following steps: Step 1: Screening the powders required for each part of the Ti-Zr-Mo gradient titanium alloy Spherical Ti powder, Zr powder and Mo powder with a particle size range of 75 μm to 150 μm are screened out respectively, heated to 120°C under a vacuum condition of ≤133Pa, and then kept warm for 120 to 180 minutes, and then cooled to room temperature under the same vacuum environment to remove moisture from the powder. Among them, the three powders of Ti, Zr and Mo are weighed according to the proportion and loaded into an agate ball mill jar, and then put into a planetary ball mill for mixing. The parameters are set to a frequency of 25 Hz and a time of 120 minutes; specifically, the powder is preferably a spherical powder prepared by a rotating electrode melting method.
[0032] Step 2: Determine the forming parameters of the gradient titanium alloy The optimal laser power for gradient titanium alloy is 3800 W, the optimal laser scanning speed is 10 mm / s, the optimal powder feeding rate is 15 g / min, the optimal gas flow rate is 4 L / min, the optimal nozzle lifting height per layer is 0.8 mm, the adjacent track overlap rate is 50%, and the spot diameter is 5 mm.
[0033] Step 3: Forming Ti-Zr-Mo gradient titanium alloy The powder from step 1 was prepared by laser directed energy deposition according to the parameters of step 2, and the oxygen content of the atmosphere was kept at 1000-2000 ppm during the deposition process. During the deposition process, the weight of the powder fed into the molten pool was controlled by adjusting the rotation speed of the powder feeder turntable, thereby achieving a gradient change in the alloy sample.
[0034] Step 3: The laser directional energy deposition method is performed on an optical fiber or a semiconductor laser. A pure titanium rolled plate is used as a substrate material and is used after being polished and cleaned.
[0035] Step 4: subjecting the formed sample obtained in step 3 to solid solution quenching treatment.
[0036] Step 5, cut part of the formed sample obtained in step 4 along the gradient direction, grind and polish it, and then measure the hardness every 1 mm along the gradient direction to obtain the Vickers hardness value, and finally obtain the hardness change curve of the gradient sample along the gradient direction.
[0037] Step six, scanning and observing the samples obtained in steps four and five along the gradient direction to obtain the composition change curve and microstructure change map of the gradient alloy.
[0038] Step seven, combining the results of step five and step six, determine the optimal alloy composition range.
[0039] A third aspect of the present invention provides a low modulus, high strength, metastable β titanium alloy for use in biomedicine, aerospace, automobile manufacturing or machinery manufacturing.
[0040] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0041] Example 1 This embodiment uses a rotating electrode method to prepare spherical powder, and the particle size and composition of the powder are shown in Table 1.
[0042] Table 1 Powder specifications
[0043] Powders with a particle size range of 75 μm to 150 μm were screened out from three pure metal powders and placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133 Pa, then kept warm for 120 minutes, and cooled to room temperature under a vacuum environment. After the powders were cooled to room temperature, they were immediately taken out of the vacuum drying oven and added to the three powder feeders of the laser directed energy deposition equipment. The powder feeders used high-purity argon (purity 99.999%) to transport the powders, and the powder-carrying airflow was 5 L / min.
[0044] The surface of the pure titanium rolled substrate was polished with 400-mesh sandpaper, and then the substrate was cleaned with acetone to remove surface oil impurities. Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3800 W, a scanning speed of 600 mm / min, a powder feeding rate of 15 g / min, an overlap rate of 50%, a lift of 0.8 mm, and an interlayer rotation angle of 90°.
[0045] By adjusting the turntable speed, the weight of powder fed into the molten pool in each direction is controlled, and gradient changes are realized in sequence. At the beginning, the turntable speed of Ti powder of No. 1 powder feeding barrel is set to 6 rpm, the turntable speed of Zr powder of No. 2 powder feeding barrel is set to 1 rpm, and the turntable speed of Mo powder of No. 3 powder feeding barrel is set to 0.5 rpm. After depositing four layers continuously, the turntable speed is adjusted to set the turntable speed of Ti powder of No. 1 powder feeding barrel to 5.8 rpm, the turntable speed of Zr powder of No. 2 powder feeding barrel remains unchanged, and the turntable speed of Mo powder of No. 3 powder feeding barrel is set to 0.6 rpm. After depositing four layers again, the turntable speed is adjusted, and this is repeated until the deposition is completed.
[0046] After forming, the sample was placed in a forming chamber filled with Ar gas to cool naturally, and then taken out after cooling to room temperature to obtain a Ti-Zr-Mo gradient titanium alloy. Figure 1 As shown, the sample size is 20 mm × 20 mm × 40 mm. The obtained sample is subjected to solution quenching treatment, the solution temperature is 800 ° C, the solution time is 60 minutes, and then taken out and water quenched.
[0047] Part of the formed sample was cut along the gradient direction. After grinding and polishing, the Vickers hardness value was obtained every 1 mm along the gradient direction. The corresponding microstructure and composition were obtained by scanning electron microscopy and energy spectrum. Finally, the hardness change curve and composition change curve of the gradient sample along the gradient direction were obtained.
[0048] The composition of the Ti-Zr-Mo gradient titanium alloy obtained in this embodiment varies as follows: Figure 2As shown in (a), as the distance from the substrate increases, the Mo content gradually increases, the Ti content gradually decreases, and the Zr content remains almost stable. This shows that the alloy changes according to the preset gradient, which is in line with the experimental design. The alloy hardness change curve is shown in Figure 2 As shown in (b), with the increase of the distance from the substrate, the hardness of the gradient alloy increases first, then decreases, and then gradually tends to be stable. This is because with the increase of the Mo content, the solid solution strengthening effect of the element is gradually enhanced, resulting in a gradual increase in the alloy hardness. Mo is a strong β-stabilizing element. When it exceeds a certain concentration, the alloy gradually transforms from α phase to β phase, the α phase gradually decreases, and the β phase content gradually increases, causing the alloy hardness to begin to decrease, and finally transform into a full β phase, and the alloy hardness tends to be stable.
[0049] The microstructures corresponding to some components are as follows Figure 3 As shown, it can be seen that when the alloy is close to the substrate, that is, when the Mo content is low, it is an α+β phase, and is mainly composed of fine α phase. As the Mo content increases, the β phase gradually increases, and finally the alloy presents a full β structure.
[0050] According to the hardness variation law and the corresponding organization, Ti-24Zr-11Mo was selected as the experimental composition, which is composed of the following mass fractions: Mo 11%, Zr 24%, and the balance Ti; Weigh the three powders of Ti, Zr and Mo according to the weight percentage, put the powder into the agate ball mill and mix the powder using a planetary ball mill. The mixing time is 120 minutes and the parameter frequency is set to 25Hz. Place the mixed powder in a vacuum drying oven, heat it to 120℃ under vacuum conditions of ≤133Pa, then keep it warm for 120 minutes and cool it to room temperature under vacuum. After the powder cools to room temperature, take it out of the vacuum drying oven and put it into the powder feeder.
[0051] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3800 W, a scanning speed of 600 mm / min, an overlap rate of 50%, a lift of 0.8 mm, and an interlayer rotation angle of 90°.
[0052] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out. Figure 4 The microstructure of the Ti-24Zr-11Mo alloy prepared in Example 1 is composed of all β structures. Figure 5 These are the diffraction spots of the Ti-24Zr-11Mo alloy prepared in Example 1. It can be seen from the calibration that the alloy is all β phase.
[0053] The mechanical properties of the Ti-24Zr-11Mo alloy prepared in Example 1 were tested in accordance with the national standard GB / T 228.1-2010 “Tensile test of metallic materials Part 1 Room temperature test method”.
[0054] Figure 6 This is the tensile mechanical property curve of the Ti-24Zr-11Mo alloy prepared in Example 1. The tensile yield strength and tensile strength of the Ti-24Zr-11Mo alloy are comparable to those of the Ti6Al4V alloy, and the elastic modulus is reduced by more than 45%, which can effectively reduce the "stress shielding effect" of the implant and provide sufficient support strength.
[0055] Table 2 Room temperature tensile mechanical properties of the alloy in Example 1
[0056] Example 2 The same ingredient screening method and ingredients as in Example 1 were used.
[0057] The Ti-24Zr-11Mo components were screened, and the three powders were weighed according to the weight percentage. The powders were placed in an agate ball mill and mixed using a planetary ball mill. The mixing time was 120 minutes, with the forward and reverse rotations alternating for 20 minutes each. The mixed powders were placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133Pa, then kept warm for 120 minutes, and cooled to room temperature under a vacuum environment. After the powders cooled to room temperature, they were immediately taken out of the vacuum drying oven and placed in a powder feeder.
[0058] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3600 W, a scanning speed of 480 mm / min, a powder feeding rate of 13 g / min, an overlap rate of 50%, a lifting amount of 0.6 mm, and an interlayer rotation angle of 90°.
[0059] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The microstructure of the Ti-24Zr-11Mo alloy prepared in Example 2 is composed of all β structures.
[0060] The mechanical properties of the Ti-24Zr-11Mo alloy prepared in Example 2 were tested in accordance with the national standard GB / T 228.1-2010 “Tensile test of metallic materials Part 1: Room temperature test method”. Figure 7 This is the tensile stress-strain curve of the Ti-24Zr-11Mo alloy prepared in Example 2.
[0061] Table 2 shows the room temperature tensile properties of the deposited Ti-24Zr-11Mo alloy. The tensile yield strength and tensile strength of the Ti-24Zr-11Mo alloy are comparable to those of the Ti6Al4V alloy, and the elastic modulus is significantly reduced, which can effectively reduce the "stress shielding effect" of the implant and provide sufficient support strength.
[0062] Table 3 Room temperature tensile mechanical properties of the alloy in Example 2
[0063] Example 3 The same ingredient screening method and ingredients as in Example 1 were used.
[0064] The Ti-24Zr-11Mo components were screened, and the three powders were weighed according to the weight percentage. The powders were placed in an agate ball mill and mixed using a planetary ball mill. The mixing time was 120 minutes, with the forward and reverse rotations alternating for 20 minutes each. The mixed powders were placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133Pa, then kept warm for 120 minutes, and cooled to room temperature under a vacuum environment. After the powders cooled to room temperature, they were immediately taken out of the vacuum drying oven and placed in a powder feeder.
[0065] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3400 W, a scanning speed of 480 mm / min, a powder feeding rate of 10 g / min, an overlap rate of 50%, a lifting amount of 0.6 mm, and an interlayer rotation angle of 90°.
[0066] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0067] Figure 8 This is the XRD spectrum of the Ti-24Zr-11Mo alloy prepared in Example 3, indicating that the alloy is composed of all-β structure.
[0068] The mechanical properties of the Ti-24Zr-11Mo alloy prepared in Example 3 were tested in accordance with the national standard GB / T 228.1-2010 “Tensile test of metallic materials Part 1: Room temperature test method”.
[0069] Table 4 shows the tensile mechanical properties of the Ti-24Zr-11Mo alloy prepared in Example 3 divided into three pieces. The tensile yield strength and tensile strength of the Ti-24Zr-11Mo alloy are comparable to those of the Ti6Al4V alloy, and the elastic modulus is significantly reduced, which can effectively reduce the "stress shielding effect" of the implant and provide sufficient support strength.
[0070] Table 4 Room temperature tensile mechanical properties of the alloy in Example 3
[0071] It should be noted that in Example 1, the mechanical properties of the Ti-24Zr-11Mo sample after directed energy deposition + solution quenching heat treatment were measured, in Example 2, the mechanical properties of the Ti-24Zr-11Mo sample after directed energy deposition were measured, and in Example 3, the sample preparation parameters used for the Ti-24Zr-11Mo sample were different from those in Example 1.
[0072] Example 4 The same component screening method as in Example 1 was used, and the screened component was Ti-20Zr-12Mo, which specifically consisted of the following components by mass fraction: Mo 12%, Zr 20%, and the balance Ti; The Ti-20Zr-12Mo components were screened, and the three powders were weighed according to the weight percentage. The powders were placed in an agate ball mill and mixed using a planetary ball mill. The mixing time was 120 minutes, with forward and reverse rotations alternating for 20 minutes each. The mixed powders were placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133Pa, then kept warm for 120 minutes, and cooled to room temperature under a vacuum environment. After the powders cooled to room temperature, they were immediately taken out of the vacuum drying oven and placed in a powder feeder.
[0073] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3800 W, a scanning speed of 600 mm / min, a powder feeding rate of 13 g / min, an overlap rate of 50%, a lifting amount of 0.6 mm, and an interlayer rotation angle of 90°.
[0074] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0075] The microstructure of the Ti-20Zr-12Mo alloy prepared in Example 4 consists of all-β structure.
[0076] The mechanical properties of the Ti-20Zr-12Mo alloy prepared in Example 1 were tested in accordance with the national standard GB / T 228.1-2010 “Tensile test of metallic materials Part 1: Room temperature test method”.
[0077] The tensile yield strength and tensile strength of Ti-20Zr-12Mo alloy are comparable to those of Ti6Al4V alloy, and the elastic modulus is significantly reduced, which can effectively reduce the "stress shielding effect" of implants and provide sufficient support strength.
[0078] Table 5 Room temperature tensile mechanical properties of the alloy in Example 4
[0079] Example 5 The same component screening method as in Example 1 was used, and the screened component was Ti-20Zr-12Mo, which specifically consisted of the following components by mass fraction: Mo 12%, Zr 20%, and the balance Ti; The Ti-20Zr-12Mo components were screened, and the three powders were weighed according to the weight percentage. The powders were placed in an agate ball mill and mixed using a planetary ball mill. The mixing time was 120 minutes, with forward and reverse rotations alternating for 20 minutes each. The mixed powders were placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133Pa, then kept warm for 120 minutes, and cooled to room temperature under a vacuum environment. After the powders cooled to room temperature, they were immediately taken out of the vacuum drying oven and placed in a powder feeder.
[0080] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3600 W, a scanning speed of 600 mm / min, a powder feeding rate of 13 g / min, an overlap rate of 50%, a lifting amount of 0.6 mm, and an interlayer rotation angle of 90°.
[0081] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0082] The microstructure of the Ti-20Zr-12Mo alloy prepared in Example 5 consists of all-β structure.
[0083] Example 6 The same component screening method as in Example 1 was used, and the screened component was Ti-24Zr-11Mo, which specifically consisted of the following components by mass fraction: Mo 11%, Zr 24%, and the balance Ti; The Ti-24Zr-11Mo composition was screened, and the pre-alloyed powder was used for forming experiments. The powder was placed in a vacuum drying oven, heated to 120 °C under a vacuum condition of ≤133Pa, then kept warm for 120 min, and cooled to room temperature under vacuum. After the powder cooled to room temperature, it was immediately taken out of the vacuum drying oven and placed in a powder feeder.
[0084] Laser directed energy deposition was carried out in a protective atmosphere of high-purity argon (purity 99.999%). The laser was a fiber laser with a spot diameter of 5 mm, a laser power of 3600 W, a scanning speed of 600 mm / min, a powder feeding rate of 13 g / min, an overlap rate of 50%, a lifting amount of 0.6 mm, and an interlayer rotation angle of 90°.
[0085] The deposited sample is a block sample of 70 mm×30 mm×25 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0086] Example 7 The same component screening method as in Example 1 was used, and the screened component was Ti-24Zr-11Mo, which specifically consisted of the following components by mass fraction: Mo 11%, Zr 24%, and the balance Ti; Ti-24Zr-11Mo components were screened and pre-alloyed powder was used for the experiment. The powder particle size was 15-53μm. The powder was placed in a vacuum drying oven and heated to 120°C under vacuum conditions of ≤133Pa, then kept warm for 120 min and cooled to room temperature under vacuum. After the powder cooled to room temperature, it was immediately taken out of the vacuum drying oven and placed in a powder bin.
[0087] In the protective atmosphere of high-purity argon (purity 99.999%), laser powder bed fusion method was used for additive manufacturing. The laser spot diameter was 60 μm, the laser power was 210 W, the scanning speed was 1200 mm / s, the scanning spacing was 100 μm, the layer thickness was 30 μm, and the interlayer rotation angle was 90°.
[0088] The sample is a block sample of 60 mm×10 mm×10 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0089] Example 8 The same component screening method as in Example 1 was used, and the screened component was Ti-24Zr-11Mo, which specifically consisted of the following components by mass fraction: Mo 11%, Zr 24%, and the balance Ti; The Ti-24Zr-11Mo composition was screened and pre-alloyed powder was used for the experiment. The powder particle size was 15~53μm. The powder was placed in a vacuum drying oven and heated to 120℃ under vacuum conditions of ≤133Pa, then kept warm for 120 min and cooled to room temperature under vacuum. After the powder cooled to room temperature, it was immediately taken out of the vacuum drying oven and placed in a powder bin.
[0090] The laser powder bed fusion method was used for preparation under the protective atmosphere of high-purity argon (purity 99.999%). The process parameters were as follows: laser spot diameter of 60 μm, laser power of 240 W, scanning speed of 1500 mm / s, scanning spacing of 80 μm, layer thickness of 45 μm, and interlayer rotation angle of 90°.
[0091] The sample is a block sample of 60 mm×10 mm×10 mm. The sample is solution quenched at a solution temperature of 800℃ and a solution time of 60 minutes, and then water quenched after being taken out.
[0092] In order to illustrate the relevant properties of a low modulus, high strength, metastable β titanium alloy provided by the present invention, an explanation is given in combination with the prior art.
[0093] In the literature “PA Kuroda, Effect of molybdenum on structure, microstructure and mechanical properties of biomedical Ti-20Zr-Mo alloys, Materials Science and Engineering: C, 2016, 67: 511-515”, Kuroda et al. studied the elastic modulus of Ti-20Zr alloy and found that without adding other elements such as Mo, the alloy is mainly α' phase with an elastic modulus of 97±3GPa, which has no significant change compared with Ti6Al4V. It still produces a "stress shielding" effect and is not suitable for bone implants. In the literature “N. Kang, Microstructure and tensile properties of Ti-Mo alloys manufactured via using laser powder bed fusion, Journal of Alloys and Compounds, 2019, 771: 877-884”, Kang et al. studied Ti-7.5Mo and found that the alloy elastic modulus was 70.6GPa, the yield strength was only 560MPa, and the elongation was only 9.2%.
[0094] According to the molybdenum equivalent formula Mo eq=1.0 [Mo] + 0.2 [Ta]+ 0.28 [Nb] + 0.4 [W]+ 0.67 [V] +1.25 [Cr]+ 1.25 [Ni] +1.7 [Mn]+ 1.7 [Co] + 2.5 [Fe]. It can be seen that Mo is a strong β-stabilizing element. By adding an appropriate amount of Mo, the β phase in the alloy can be stabilized, thereby reducing the elastic modulus of the alloy. However, when the Mo content increases beyond a certain range, the elastic modulus of the alloy increases instead. This is because the excess Mo atoms increase the bonding force between atoms, thereby increasing the elastic modulus. Therefore, there is a suitable range for the addition of Mo. Zr and Ti can form an infinite solid solution, thereby increasing the strength of the alloy through solid solution strengthening. At the same time, Zr has the effect of refining grains, increasing the strength of the alloy through fine grain strengthening. When the third element exists, Zr can also play a role in reducing the elastic modulus of the alloy. Therefore, through the joint action of Zr and Mo elements, the preparation of low-modulus and high-strength titanium alloys can be achieved.
[0095] The literature "CL Zhao, Mechanical and electrochemical characterization of Ti-12Mo-5Zr alloy for biomedical application, Journal of Alloys and Compounds, 2011, 509: 8235-8238" reported that the elastic modulus of Ti-12Mo-5Zr alloy after solution treatment at 1053K was 78.6GPa, while the yield strength was only 540MPa, the ultimate tensile strength was 695MPa, and the elongation was only 3.9%. After solution treatment at 1133K, the elastic modulus of the alloy was 64.5GPa, while the yield strength was only 509MPa, the ultimate tensile strength was 628MPa, and the elongation was only 4.7%. Among the components provided by the present invention, Ti-24Zr-11Mo, after directed energy deposition and solution quenching treatment, can reach an elastic modulus of 59.9 GPa, which is nearly 50% optimized compared to Ti6Al4V alloy, while maintaining a yield strength of 842.1 MPa, comparable to Ti6Al4V alloy, a tensile strength of 897.2 MPa, and an elongation of 15.9%. Its comprehensive performance indicators are far superior to Ti6Al4V alloy and the components reported in the literature.
[0096] In summary, the present invention provides a low modulus, high strength, metastable β titanium alloy, the mass fraction of its alloy components is: Mo 10.5% ~ 12%, Zr 20% ~ 25%, and the balance is Ti. The titanium alloy provided by the present invention does not add expensive alloying elements such as Nb, Ta, etc., and through additive manufacturing and post-heat treatment, the microstructure of the titanium alloy finally formed is a full β structure, and finally after laser directional energy deposition forming and solution quenching, an elastic modulus of 59.9 ~ 74.2GPa, a yield strength of 800 ~ 880MPa, a tensile strength of 840 ~ 950MPa and an elongation of 13% ~ 20% can be directly obtained, and its mechanical properties can meet the needs of implants in biomedicine, and can effectively reduce the occurrence of "stress shielding effect" and provide sufficient strength support. The results of the present invention have broad application prospects in the field of biomedicine and can significantly improve production efficiency and economic benefits. The present invention also provides a design method for the composition and process of a low-modulus, high-strength metastable β titanium alloy. By combining high-throughput experimental technology and directed energy deposition technology, a low-modulus, high-strength titanium alloy composition dedicated to laser additive manufacturing is explored. A Ti-Zr-Mo composition gradient alloy is prepared in situ by multi-channel coaxial powder feeding, and the change in the gradient mechanical properties of the alloy is characterized by hardness. The low value point of the hardness curve is selected as the composition point to obtain a metastable β titanium alloy with low modulus and high strength performance.
[0097] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low modulus, high strength, metastable β titanium alloy, characterized in that: It is composed of the following components in mass fractions: Mo 10.5%~12%, Zr 20%~25%, and the balance Ti.
2. The low modulus, high strength, metastable β titanium alloy according to claim 1, characterized in that: The elastic modulus of the low-modulus high-strength metastable β titanium alloy is 59.9-74.2 GPa.
3. The low modulus, high strength, metastable β titanium alloy according to claim 1, characterized in that: The low modulus high strength metastable β titanium alloy has a yield strength of 800-880 MPa, a tensile strength of 840-950 MPa, and an elongation of 13%-20%.
4. The low modulus, high strength, metastable β titanium alloy according to claim 1, characterized in that: The alloy structure of the low-modulus high-strength metastable β titanium alloy in the deposited state and the solid solution quenched state is β phase.
5. A method for preparing the low modulus, high strength, metastable β titanium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing Ti powder, Zr powder and Mo powder according to a certain proportion to obtain a mixed powder; or preparing a TiZrMo component pre-alloyed powder; After the mixed powder or pre-alloyed powder is vacuum dried, a sample is formed on a pure titanium substrate by laser directed energy deposition or laser powder bed melting. After forming, a solution quenching treatment is performed to obtain a low-modulus and high-strength metastable β titanium alloy.
6. The method for preparing a low modulus high strength metastable β titanium alloy according to claim 5, characterized in that: When Ti powder, Zr powder and Mo powder are mixed according to the proportion, it includes: Ti powder, Zr powder and Mo powder were weighed according to the proportion and loaded into an agate ball mill jar, and then put into a planetary ball mill for mixing. The parameters were set to a frequency of 25 Hz and a time of 120 minutes.
7. The method for preparing a low modulus high strength metastable β titanium alloy according to claim 5, characterized in that: When depositing powder by laser directed energy deposition, the process parameters include: The laser spot diameter is 5 mm, the laser power is 3400~3800 W, the laser beam scanning speed is 8~10 mm / s, the overlap rate is 50%, the powder feeding rate is 10~15 g / min, the gas flow rate is 4~5 L / min, and the nozzle lifting height per layer is 0.6~0.8 mm; Wherein, when using the laser directed energy deposition method, the particle size of the Ti powder, Zr powder, and Mo powder in the mixed powder or the particle size of the pre-alloyed powder is 75-150 μm.
8. The method for preparing a low modulus high strength metastable β titanium alloy according to claim 5, characterized in that: During solution quenching treatment, the solution temperature is 750~850℃ and the solution time is 40~120min.
9. The method for preparing a low modulus high strength metastable β titanium alloy according to claim 5, characterized in that: The process parameters for preparing high-strength titanium alloy workpieces by laser powder bed fusion are: The laser spot diameter is 60 μm, the laser power is 200~240W, the laser scanning speed is 1000~1500 mm / s, the layer thickness is 30~45 μm, and the scanning line distance is 80~100 μm; Among them, when using the laser powder bed melting method, the particle size of the Ti powder, Zr powder, Mo powder or pre-alloyed powder in the mixed powder is 15~53μm.
10. Use of the low modulus, high strength, metastable β titanium alloy according to any one of claims 1 to 4 in biomedicine, aerospace, automobile manufacturing or machinery manufacturing.
Citation Information
Patent Citations
High-strength-toughness corrosion-resistant beta-type titanium-zirconium-based alloy and preparation method thereof
CN112176220A
Additive-manufactured metastable beta titanium alloy with ultrahigh yield strength and high plasticity
CN113832369A
Biomedical titanium alloy with excellent elastic modulus and construction and preparation method thereof
CN115410670A
Titanium alloy tissue regulation and control method and application of titanium alloy tissue regulation and control method in field of medical implants
CN117070789A
Additive manufacturing high-fatigue-strength titanium alloy and preparation method thereof
CN117467867A
Cited By
Titanium alloy based on laser powder bed melting and preparation method thereof
CN122446005A
